EMPOWERING STUDENTS' CRITICAL LITERACY THROUGH MULTIMODALITY APPROACH AT A SENIOR HIGH SCHOOL IN AMBON - Felicia Miranda Lekatompessy; Jusak Patty; Annery Fienta (Universitas Pattimura, 2026)
This community service program aimed to strengthen students' critical literacy through multimodal English learning supported by artificial intelligence (AI) at SMA Negeri 6 Ambon. The program was implemented through four stages: orientation and coordination, training implementation, mentoring and evaluation, and sustainability planning. Students analysed videos, posters, and social media texts before creating thematic multimodal posters, which were later enhanced using AI tools such as Gemini and Google AI Studio. Observations and participant feedback showed increased engagement during collaborative activities, with students demonstrating greater confidence in interpreting visual messages and expressing ideas across modes. Teachers noted that multimodal tasks encouraged more active participation compared to conventional learning activities. The findings indicate that integrating critical literacy, multimodality, and guided AI use can support contextual English learning and promote meaningful student involvement in local EFL classrooms.